Horses & Ponies Learn to paint a range of breeds step by step - Harrison, Lesley (California, USA Walter Foster Publishing, 2013)
understanding pastels - capturing personality painting horses in action - creating dynamic composition
Arts ( Drawing )
1 13
Keywords: Animal painting; Drawing; painting